2013
DOI: 10.1002/jcb.24472
|View full text |Cite
|
Sign up to set email alerts
|

Role of JAK2–STAT3 in TLR2‐mediated tissue factor expression

Abstract: Tissue factor (TF) is a core protein with an essential function in the coagulation cascade that maintains the homeostasis of the blood vessels. TF not only participates in neointima formation, but also causes the development of atherosclerosis. This study investigated the mechanism regulating TF expression in macrophages using Pam3 CSK4 , a TLR2 ligand. Pam3 CSK4 induced TF expression in two types of macrophages (Raw264.7 and BMDM), but not in TLR2 KO mice derived BMDM. Pam3 CSK4 induced TF expression was inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…Wang et al highlighted the role of JAK3 in regulation of TLR‐mediated inflammatory cytokine production [Wang et al, ]. Our previous report also showed the importance of JAK2‐STAT3 pathway in TLR2‐mediated tissue factor expression [Park et al, ]. Another example is that STAT1 plays a role in TLR signaling and inflammatory response [Luu et al, ].…”
Section: Discussionmentioning
confidence: 94%
“…Wang et al highlighted the role of JAK3 in regulation of TLR‐mediated inflammatory cytokine production [Wang et al, ]. Our previous report also showed the importance of JAK2‐STAT3 pathway in TLR2‐mediated tissue factor expression [Park et al, ]. Another example is that STAT1 plays a role in TLR signaling and inflammatory response [Luu et al, ].…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, treatment of the cells with Pam 3 CSK 4 markedly increased the mRNA expression of MCP-1 in a time-dependent manner. TF is a major risk factor for atherosclerosis, and lectin-Lox-1 is also crucial in oxidized-LDL-mediated atherosclerosis (14,16). Therefore, the present study measured changes in the expression levels of these two genes following TLR2 stimulation.…”
Section: Inflammatory Mediators Are Upregulated By Tlr2 Stimulationmentioning
confidence: 97%
“…Among TLRs, TLR2 is also involved in the progression of atheroma. A previous study reported that TLR2 is a receptor for foam cell formation (13,14); therefore, the present study attempted to determine the role of TRIF in TLR2-mediated foam cell formation using the siRNA technique. Compared with the control siRNA-transfected cells, the TRIF-siRNA transfected cells showed decreased mRNA expression of TRIF.…”
Section: Trif Is Involved In Tlr2-induced Foam Cell Formationmentioning
confidence: 99%
“…11 NF-κB is the molecular target of ROS and is involved in vascular inflammation. 43 Finally, the IL-6 dependent JAK/STAT pathway was examined by a western blot assay. 40 TF, a 47 kDa protein, regulated by the transcription factors, NF-κB and AP-1/c-JUN, is the primary activator of the coagulation cascade.…”
Section: Papermentioning
confidence: 99%